2009
DOI: 10.1088/0004-6256/137/6/4670
|View full text |Cite
|
Sign up to set email alerts
|

Heracles: The Hera Co Line Extragalactic Survey

Abstract: We present the HERA CO-Line Extragalactic Survey (HERACLES), an atlas of CO emission from 18 nearby galaxies that are also part of The H I Nearby Galaxy Survey (THINGS) and the Spitzer Infrared Nearby Galaxies Survey (SINGS). We used the HERA multi-pixel receiver on the IRAM 30-m telescope to map the CO J = 2 → 1 line over the full optical disk (defined by the isophotal radius r 25 ) of each target, at 13 ′′ angular resolution and 2.6 km s −1 velocity resolution. Here we describe the observations and reduction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

65
871
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 626 publications
(960 citation statements)
references
References 37 publications
65
871
13
Order By: Relevance
“…2 shows that Σco(R) is depressed at small radii relative to an exponential radial distribution, as was also pointed out by Regan et al (2001) and Helfer et al (2003). Exponential distributions are traditionally used for fitting the radial profiles of CO surface brightness observed in nearby galaxies, and thus for inferring important physical parameters such as the scale length of the molecular disc and, when relevant, its central surface density (e.g., Young & Scoville 1982;Young et al 1995;Sakamoto et al 1999;Regan et al 2001;Helfer et al 2003;Leroy et al 2008Leroy et al , 2009). Fig.…”
Section: Molecular Gasmentioning
confidence: 56%
“…2 shows that Σco(R) is depressed at small radii relative to an exponential radial distribution, as was also pointed out by Regan et al (2001) and Helfer et al (2003). Exponential distributions are traditionally used for fitting the radial profiles of CO surface brightness observed in nearby galaxies, and thus for inferring important physical parameters such as the scale length of the molecular disc and, when relevant, its central surface density (e.g., Young & Scoville 1982;Young et al 1995;Sakamoto et al 1999;Regan et al 2001;Helfer et al 2003;Leroy et al 2008Leroy et al , 2009). Fig.…”
Section: Molecular Gasmentioning
confidence: 56%
“…Utilizing data from the THINGS, HERACLES, and BIMA SONG surveys Leroy et al, 2009;Helfer et al, 2003), Bigiel et al (2008) investigated the resolved star formation law in nearby galaxies. These authors found that the SFR is principally correlated with H 2 gas (as traced by CO (J=2-1) in this case), and unassociated with HI in nearby galaxies.…”
Section: Star Formation Laws and Efficienciesmentioning
confidence: 99%
“…The most common approach to deal with this issue is to apply an aperture correction to the CO flux measurements. This is frequently done by utilising resolved CO maps of similar sources (Regan et al 2001;Kuno et al 2007;Leroy et al 2009) to estimate the amount of missed flux (Bothwell et al 2013;Saintonge et al 2011a), assuming a smooth gas profile which follows the distribution of stellar light. However, studies based on both isothermal simulations and spatially resolved maps show that during a galaxy encounter the distribution of molecular gas is less uniform, with CO emission located along tidal features, dust lanes or in extended disks (Shlosman et al 1989;Konig et al 2014;Ueda et al 2014 Kauffmann et al (2003) classification, by using the SFR-D4000 relation (Brinchmann et al 2004).…”
Section: Galaxy Pairs Xcoldgassmentioning
confidence: 99%